RATIONAL USE OF BIOLOGICAL RESOURCES - G’.Mahkamov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article describes the importance of biological and natural resources. The importance of plants in human life.